Effect of eWOM stimuli and eWOM response on perceived service quality and online recommendation. Issue 4 (2nd October 2021) - Roy, Gobinda; Datta, Biplab; Mukherjee, Srabanti; Basu, Rituparna
ABSTRACT: In congruence with the remarkable trend of consumer's adoption of online hotel booking services, this study applies the Stimulus-Organism-Response (S-O-R) framework to analyse the direct triadic effect of electronic Word-of-Mouth (eWOM) stimuli including valence, volume, and image review on customer's perceived service quality. Consequent effects of perceived service quality on the online recommendation intention of the customer are measured along with moderating effects of the hotel's eWOM response. In a single integrated framework, we conceptualised and examined the effects of stimuli (volume, valence and image-based view) on the organism (perceived service quality) and its subsequent effect on customer's response in the form of recommendation intention. The results from the multiple regression analysis (with interaction effect) indicated the significant role of the eWOM stimuli in forming perceived service quality. As a novel contribution, this study identifies that eWOM response moderates the effect of eWOM stimulus on perceived service quality and online recommendation. Managerial implications are discussed.